FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN TPI TASIK AGUNG REMBANG - Muhammad Najikh Abdillah; Hawik Ervina; Ira Setiawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to determine the influence of organizational culture, job engagement, organizational environment on the performance of Tpi Tasik Agung Rembang employees. This type of research uses quantitative research methods and the data used in this study is primary data. The population in this study was TPI Tasik Agung Rembang, this study used non-probability techniques with a saturated sample of 80 respondents. The measurement of this study used a Likert scale which was then processed with the IBM SPSS Statistical Version 25 analysis tool using multiple linear analysis. The results of this study show that there is a positive and significant influence between organizational culture and performance partially, job engagement has a positive and significant effect on performance partially, the organizational environment has a positive and significant effect on performance partially. The results of the coefficient of determination (R2) test obtained a value from Ajusted R Square of 0.341 or 34.1% showed that performance variables were influenced by organizational culture variables, job engagement, organizational environment while 65.9% were influenced by other variables